Standard Forms of Contract Selection Criteria: A Qualitative Analysis of the Western Australian Construction Industry - Whyte, Andrew; MacPherson, Erin (RICS, 2011)
Opportunities exist for a new structured decision-making criteria guide, towards selection of the most appropriate standard form of contract, in a given environment, for the West Australian (WA) civil-engineering/construction industry; the work presented describes decisions required to choose an effective standard form of contract (from a wide array of options) and the factors that influence these decisions. Secondary research identified a lack of structured guidance available locally, paving the way towards primary research, in conjunction with stakeholders in the Australian engineering construction industry, in the development of a new guidance tool. Data collected, analysed as part of a qualitative research methodology, provided the findings to develop subsequently a practical, objective, and structured standard form of contract selection guide for use within the local construction industry. The decision flow chart developed as part of this research is expected to improve the speed and accuracy in the choice of which standard form of contract is most suitable from the wide range of available options. This guide may also serve as a contract training aid for graduate civil-engineers involved in procurement activities in the construction industry.